Analisis Kebijakan Perpajakan Dan Retribusi Dalam Pemberdayaan Petani Mandiri Kelapa Sawit - Wulandari, Putri (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2015)
Crude Palm Oil (CPO) produced by Indonesia comes from three oil palm plantations, namely smallholder, State Big Plantation, and Privte Big Plantation. The amount of the contribution of palm oil produced by farmers, through smallholders shows that smallholders have a strategic role. In order to balance the involvement of farmers in palm oil bussiness, which is not only dominanted by the large farmers, the independen small farmers' competitiveness needs to be increased. This study was conducted to determine the government's efforts in empowering the independent oil palm farmers, especially in taxes and retributions. The recommendations were made as follows. First, the local government must eliminate all forms of retributions that do not fit on Taxes and Retributions’s policy. Thus the region which is still put on retriburion on the plantation business permit and the letter of plantation business listing needs to erase it immediately. Second, the Local Government eliminate the double tax that burden the farmer by eliminating eliminate illegal levies usually done by middlemen with reason as the contribution payment of VAT CPO. Third, the government should review the policies on taxes and charges in connection with the government's efforts to improve the competitiveness of processed palm oil products.